Validating the Health Benefits of Coffee Berry Pulp Extracts in Mice with High-Fat Diet-Induced Obesity and Diabetes - Khawaja Muhammad Imran Bashir; Joo Wan Kim; Hye-Rim Park; Jae-Kyoung Lee; Beom-Rak Choi; Jae-Suk Choi; Sae-Kwang Ku (MDPI AG, 2023)
The effects of coffee (Coffea arabica L.) berry pulp extracts (CBP extracts) on the improvement of diabetes, obesity, and non-alcoholic fatty liver disease (NAFLD) were evaluated using various in vitro antioxidant activity assays and through a high-fat diet-induced mild diabetic obese mouse model. After an 84-day oral administration of CBP extracts (400-100 mg/kg), bioactivities were evaluated. The in vitro analysis showed the highest DPPH● scavenging activity of 73.10 ± 4.27%, ABTS● scavenging activity of 41.18 ± 1.14%, and SOD activity of 56.24 ± 2.81%, at a CBP extract concentration of 1000 µg/mL. The in vivo analysis of the CBP extracts showed favorable and dose-dependent anti-obesity, anti-diabetic, NAFLD, nephropathy, and hyperlipidemia refinement effects through hepatic glucose enzyme activity, 5'-AMP-activated protein kinase (AMPK) up-regulation, antioxidant activity, lipid metabolism-related gene expression, and pancreatic lipid digestion enzyme modulatory activities. This study shows that an appropriate oral dosage of CBP extracts could function as a potent herbal formulation for a refinement agent or medicinal food ingredient to control type 2 diabetes and related complications.